Sosok Ibu dalam Puisi Bunda Airmata Karya M.H. Ainun Najib dan Puisi Ibu Karya Widji Tukul: Suatu Kajian Sastra Bandingan - Nika Fisari; Yosi Wulandari (Universitas Ahmad Dahlan, 2020)
This study aims to determine the relationship of the poetry of the mother of tears by M.H Ainun Najib with the poem of the mother of Widji Tukul. Analysis in this theory uses a comparative literary theory that discusses metaphors, symbols and relevance in both poems. The method of this study uses an intertextuality approach. This research found the mother's figure as a parent and in God's eyes so that there is a relationship that connects a mother's tears in God's eyes with a mother's tears for affection for her children, namely the relation of Islamic elements in the contents of the two poems.